อุดมการณ์ทางการเมืองของมวลมหาประชาชนในวิกฤติประชาธิปไตย - Suriyasai Katasila สุริยะใส กตะศิลา (Journal of Social Development and Management Strategy, 2016)
การศึกษานี้เป็นการวิจัยเชิงคุณภาพแบบปรากฏการณ์นิยมที่ผู้วิจัยมีส่วนร่วมในเหตุการณ์ โดยมีวัตถุประสงค์เพื่อศึกษาเงื่อนไขและความเป็นมา องค์ประกอบ รูปแบบ ยุทธศาสตร์ ยุทธวิธี นวัตกรรม อัตลักษณ์ ประเด็นข้อถกเถียงสาธารณะและอุดมการณ์ทางการเมืองในการเคลื่อนไหว ผลการศึกษา พบว่าเงื่อนไขและความเป็นมาของการเคลื่อนไหวประกอบด้วย วิกฤติชาติ วิกฤติประชาธิปไตยแบบตัวแทน วิกฤติศรัทธาของประชาชนต่อกลไกของรัฐ และวิกฤติศรัทธาของประชาชนต่อรัฐบาล องค์ประกอบของการเคลื่อนไหวนี้ ได้แก่ แกนนำเวทีหลัก แกนนำองค์กรแนวร่วม เครือข่ายผู้ปฏิบัติงาน แนวร่วมทางสังคม และมวลชน รูปแบบ ยุทธศาสตร์และยุทธวิธีในการเคลื่อนไหวถูกยกระดับขึ้น 3 ระดับ ได้แก่ การต่อต้าน ร่าง พ.ร.บ.นิรโทษกรรมฯ การขับไล่รัฐบาลนางสาวยิ่งลักษณ์ และการเรียกร้องการปฏิรูปประเทศก่อนเลือกตั้ง นอกจากนี้ยังพบว่า มวลมหาประชาชนต่างจากการเคลื่อนไหวทางตะวันตก 4 ข้อ และมีนวัตกรรมการเคลื่อนไหวทั้งสิ้น 8 ข้อ และเป็นหนึ่งในอัตลักษณ์ของ กปปส. คือ การนำรวมหมู่แบบใหม่ ข้อถกเถียงสาธารณะในการเคลื่อนไหวของมวลมหาประชาชน คือ การต่อต้านร่าง พ.ร.บ.นิรโทษกรรมฯ รัฐบาลหมดความชอบธรรม และการเรียกร้องให้ปฏิรูปประเทศก่อนการเลือกตั้ง และสุดท้ายอุดมการณ์ทางการเมืองของมวลมหาประชาชนคือ “สังคมธรรมาธิปไตย/ประชาธิปไตยเชิงคุณธรรม” ซึ่งมี 2 ช่องทางที่สามารถนำไปสู่การบรรลุอุดมการณ์ได้คือ ช่องทางปฏิรูปประชาธิปไตยในระบบรัฐสภาตามการเมืองปกติและช่องทางประชาธิปไตยทางตรงโดยการเคลื่อนไหวเรียกร้องของมวลชนนอกสภาฯ คำสำคัญ มวลมหาประชาชน/กปปส. ประชาธิปไตยทางตรง การนำรวมหมู่แบบใหม่ สังคมธรรมาธิปไตย/ ประชาธิปไตยเชิงคุณธรรม Political Ideology of the People’s Democratic Reform Committee (PDRC) in Thailand’s Democratic Crisis This article is a participatory qualitative research using the phenomenology method, and had the following objectives: to study the conditions and backgrounds of the PDRC movement, the composition, forms, strategies, tactics, innovations, and identities of the PDRC movement, and the public proposals and political ideologies of this movement. The findings of this article were as follows. The conditions and backgrounds of the PDRC movement include 4 factors: national crisis, crisis of representative democracy, crisis of the people’s faith in the government sectors, and the crisis of the people’s faith in the government. The PDRC movement is composed of 5 main parts; major and co-leaders, the co-organization’s leader, operative worker networks, social alliances and mass, where the forms, strategies, and tactics of this movement were adjusted based on the objectives of the movement, which were separated into 3 main periods: opposing the amnesty bill, expelling Yingluck’s government, and proposing the political campaign called “Reform Before Election.” The differences in the social movement between the PDRC and that of Western Europe were composed of 4 points and the innovations of this movement demonstrated 8 forms. One of the main findings of this article is called “neo-collective leadership.” The public proposals for this movement were separated into 3 main points in each period, as shown above. Finally, the political ideology of this movement was Meritocracy/Moral democracy, which has two paths to fulfill; 1) the path of democratic reform in the parliamentary system and 2) the path of direct democracy via civil movement. Keywords: PDRC, Direct Democracy, Neo-collective Leadership, Meritocracy/Moral Democracy